Pengaruh Pupuk Kandang Ayam dan Ampas Kopi terhadap Tanaman Cabai Merah Keriting (Capsicum annum L.) - Septia Nur Diyaningtias; Rusmana Rusmana; Putra Utama; Dewi Firnia (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
One of the vegetable commodities with the highest economic value is chili. Optimizing the use of chicken manure and coffee grounds can increase chili yields. Using chicken manure and coffee grounds can sustainably improve plant growth and soil quality. This study used chicken manure and coffee grounds to increase the development and production of curly red chili plants until the ideal ratio of fertilizer doses and planting media was achieved. From July to October 2024, this survey was conducted on the Lambangsari Permai Housing land, Jl. Semeru II, Block B/48, Tambun Selatan District, Bekasi Regency. This study used three replications and two variables in a factorial Randomized Block Design (RAK). The first factor is the dose of chicken manure fertilizer consisting of 4 levels, namely without a dose of chicken manure fertilizer (control), 367.5 g/polybag, 735 g/polybag, and 1102.5 g/polybag, while the second factor is the dose of coffee grounds consisting of 5 levels, namely without dose of coffee grounds (control), 210.7 g/polybag, 427.525 g/polybag, 639.45 g/polybag and 877.1 g/Polybag. This process was repeated three times to produce 60 plants. This study used an ANOVA and post hoc D Multiple Range Test (DMRT) at the 5% level. Plant height, number of branches, number of fruits per plant, fruit weight, and fruit length were the characteristics measured in this study. The dose of chicken manure fertilizer has a very different impact on the development of curly red chili plants at 3 Weeks After Transplanting (MST) with 367.5 g/polybag with the best average of 18.33.